Localization of peroxisome proliferator-activated receptor alpha (PPARα) and N-acyl phosphatidylethanolamine phospholipase D (NAPE-PLD) in cells expressing the Ca2+-binding proteins calbindin, calretinin, and parvalbumin in the adult rat hippocampus - Rivera, Patricia; Arrabal, Sergio; Vargas, Antonio; Blanco Calvo, Eduardo; Serrano, Antonia; Pavon, Francisco Javier; Rodriguez de Fonseca, Fernando; Suarez, Juan (Frontiers in Neuroanatomy, 2014)
The N-acylethanolamines (NAEs) oleoylethanolamide and palmithylethanolamide are known to be endogenous ligands of PPARα receptors, and their presence requires the activation of a specific phospholipase D (NAPE-PLD) associated with intracellular Ca2+ fluxes. Thus, the identification of a specific population of NAPE-PLD/PPARα-containing neurons that express selective Ca2+-binding proteins (CaBPs) may provide a neuroanatomical basis to better understand the PPARα system in the brain. For this purpose, we used double-label immunofluorescence and confocal laser scanning microscopy for the characterization of the co-existence of NAPE-PLD/PPARα and the CaBPs calbindin D28k, calretinin and parvalbumin in the rat hippocampus. PPARα expression was specifically localized in the cell nucleus and, occasionally, in the cytoplasm of the principal cells (dentate granular and CA pyramidal cells) and some non-principal cells of the hippocampus. PPARα was expressed in the calbindin-containing cells of the granular cell layer of the dentate gyrus (DG) and the SP of CA1. These principal PPARα+/calbindin+ cells were closely surrounded by NAPE-PLD+ fiber varicosities. No pyramidal PPARα+/calbindin+ cells were detected in CA3. Most cells containing parvalbumin expressed both NAPE-PLD and PPARα in the principal layers of the DG and CA1/3. A small number of cells containing PPARα and calretinin was found along the hippocampus. Scattered NAPE-PLD+/calretinin+ cells were specifically detected in CA3. NAPE-PLD+ puncta surrounded the calretinin+ cells localized in the principal cells of the DG and CA1. The identification of the hippocampal subpopulations of NAPE-PLD/PPARα-containing neurons that express selective CaBPs should be considered when analyzing the role of NAEs/PPARα-signaling system in the regulation of hippocampal functions.